Service Quality, Price, and Product Completeness Predict Member Satisfaction in a Retail Cooperative? - Fitri Wulandari; Muhammad Imron; Novy Rachma Herawati (International Journal of Business and Quality Research, 2026)
The retail industry has remained a highly competitive sector, placing significant pressure on cooperatives to balance exclusive member services with modern retail demands. While previous studies have addressed customer satisfaction determinants in large-scale supermarkets, studies addressing this dynamic within localized cooperative retail units facing technological transitions seem sketchy. Therefore, this study examines the predictive role of service quality, price, and product completeness on member satisfaction at the KPRI Beringin retail unit in Madiun Regency, Indonesia. A cross-sectional survey design was adopted while a purposive sampling technique was used to select the study population. Validated questionnaires were used to collect data from 100 active members and analyzed using multiple linear regression to test the hypotheses. The result demonstrated that service quality, price, and product completeness simultaneously correlated with member satisfaction among study participants, R Square = 0.170, F (3, 96) = 7.752, p < 0.001. Furthermore, price emerged as the most dominant predictor of member satisfaction (beta = 0.393, p = 0.001), followed by product completeness (beta = 0.218, p = 0.045) and service quality (beta = 0.128, p = 0.032). The study concludes that economic rationality, primarily pricing, significantly contributed to member satisfaction despite operational limitations like manual cashier systems. The study recommends that cooperative stakeholders should take proactive measures to maintain competitive pricing and digitize the cashier system to enhance service efficiency.